2014
DOI: 10.1039/c4ta01711k
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon nitride nano-emitters on silicon: a photoelectrochemical heterojunction composed of earth-abundant materials for enhanced evolution of hydrogen

Abstract: Graphitic carbon nitride is a promising heterogeneous catalyst for light-induced generation of hydrogen. Here, we report the successful formation of nano-scaled carbon nitride structures on silicon, mitigating the known limitations of charge transport within bulky C-N networks. An efficient photoelectrochemical heterojunction is thereby realized, developed from earth-abundant materials only.The conversion of solar energy to chemical energy is one of the principal routes to establish a green global economy.1 Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
(42 reference statements)
2
12
0
Order By: Relevance
“…Very recently, this is also observed for a silicon-based heterocontact (7 of 9) 1402148 wileyonlinelibrary.com photocathode device consisting of ultrathin polymeric carbon nitride nanosheets on prestructured p-type silicon. [ 31 ] Here, we found also an anodic onset potential shift of ≈0.3 V of the solar hydrogen evolution as a consequence of an internal built-in voltage.…”
Section: Wileyonlinelibrarycommentioning
confidence: 90%
“…Very recently, this is also observed for a silicon-based heterocontact (7 of 9) 1402148 wileyonlinelibrary.com photocathode device consisting of ultrathin polymeric carbon nitride nanosheets on prestructured p-type silicon. [ 31 ] Here, we found also an anodic onset potential shift of ≈0.3 V of the solar hydrogen evolution as a consequence of an internal built-in voltage.…”
Section: Wileyonlinelibrarycommentioning
confidence: 90%
“…Transmission electron microscopy images for SG-CN are reported by Kailasam et al [ 2 ] Scanning electron microscopy images of photoelectrodes utilitzing PCN can be found in refs. [ 7,46,47 ] .…”
Section: Methodsmentioning
confidence: 98%
“…[ 13,17,20 ] Thus, while a well-founded transport model is still missing, Merschjann et al suggested a predominance of interplanar transport, [ 14 ] depicted in Figure 1 , together with Polymeric graphitic carbon nitrides (CN) have recently attracted considerable interest as crystalline all-organic wide-bandgap semiconductors. They have been used in a wide range of photocatalytic applications, especially for solar water-splitting, [1][2][3][4][5][6][7] as well as in photovoltaics, as tunable yellow phosphors and fl uorescent markers for bioimaging. [8][9][10][11][12] Despite the large variety of reported synthesis routes and substantial progress in characterization of the materials, the nature of charge transport in CN has not been unveiled to date.…”
Section: Doi: 101002/adma201503448mentioning
confidence: 99%
“…Lublow et al reported two‐step hydrofluoric (HF) acid etching method first to modify the silicon surface, second to under etch the g‐C 3 N 4 deposited on the Si substrate leading to nanosheets or lamellae embedded into the Si substrate for photocatalytic applications. The fabricated hybrid structure displayed rectifying heterojunction behavior, enhancing the photogenerated electron conduction toward the g‐C 3 N 4 /Si interface …”
Section: The Rise and Fall Time Corresponding To 350 680 950 And 1mentioning
confidence: 99%